The effects of stimulus repetition rate and mode of recording to OAE results - Sahal, Nur Syazana; Dzulkarnain, Ahmad Aidil Arafat (2012)
Transient evoked otoacoustic emissions (TEOAE) is one of the useful objective tests to measure the integrity of outer hair cells and has been widely used clinically. Despite its successful, the TEOAE has several limitations and one of the problems that will be addressed in this study is the interaction of test time and highly background noise to the recording. The TEOAE is susceptible to the physiological noise activities especially in children thus it is important to ensure that the recording is done quickly by presenting the stimulus more rapidly and testing both ears simultaneously (using alternating mode). This study aimed to compare TEOAE absolute amplitude and signal-to-noise ratio (SNR) results between monaural and binaural mode using standard and high rate in normal hearing subject. Thirty six normal hearing subjects (13 male and 23 female) with the mean age of 23.2 ± 1.2 year old were involved in this quasi experimental study. Prior to the testing, subjects underwent otoscopic examination, tympanometry and pure tone audiometry tests to ensure they fulfilled the inclusion criteria. Upon completing the preliminary assessments, TEOAE was conducted to each subject using 84dB pe SPL biphasic clicks stimulus with 260 trains using both monaural and binaural mode at 80 and 50 clicks per seconds. Next, the TEOAE absolute amplitude and SNR for monaural and binaural TEOAE at the same ear was analyzed and compared using RM ANOVA (95% confidence level) at each of the frequencies (1, 1.4, 2, 2.8 and 4 kHz) in both rates. RM ANOVA analysis revealed that there was no significant difference (p>0.05) between monaural and binaural TEOAE absolute amplitude on the same ear in all frequencies and both rates. In addition, there was no significant different (p >0.05) in monaural and binaural TEOAE SNR values on the same ear in all frequencies except for SNR at 1kHz and 1.4 kHz in standard rate and 1 kHz in high rate where the SNR values of monaural recording is considerably higher. In general, this study concluded that both mode of recording have similar and reliable results in both rates and therefore either mode of recordings can be used clinically.